2008
DOI: 10.1089/pho.2007.2175
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Daily Irradiation with Polychromatic Visible Polarized Light on Human Lymphocyte Populations

Abstract: The application of polychromatic visible polarized light with the aforementioned features increases the CD3(+)CD4(+) lymphocyte population. It is suggested that this regimen may be useful for the promotion of natural defenses in cell-mediated immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In this way, the inflammatory processes can be limited, and the reparative phase triggers. Our results may, in part, explain the healing of the wounded area and the improvement in chronic inflammatory processes, previously observed by us [12] and other researches [8][9][10][11][17][18][19][20][21][22] in vivo.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this way, the inflammatory processes can be limited, and the reparative phase triggers. Our results may, in part, explain the healing of the wounded area and the improvement in chronic inflammatory processes, previously observed by us [12] and other researches [8][9][10][11][17][18][19][20][21][22] in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies reporting the effects of light therapy on humans, in different pathological conditions, concern the irradiation by the application of ultraviolet (UV) lamp [1,2], infrared (IR) laser [3,4], Light Emitting Diode (LED) [5,6], and Polarized Polychromatic Incoherent Low Energy Radiation (PILER) [7][8][9][10][11]. All these sources showed light therapy exerts reparative capacity by modulating the production of cytokines and other soluble factors, and their main targets are fibroblasts from the skin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Besides an increase in absolute lymphocyte count, a recently published in-vivo study [3] also confirmed a significant elevation in the number of CD3 ? CD4 ?…”
Section: Introductionmentioning
confidence: 65%
“…In-vivo and in-vitro data [1][2][3] demonstrated that polarized light has a selective effect on the various cells of the immune response, as well as other biological model systems, in contrast to diffuse visible light of the same wavelength range and power density used as control. The experiments [2] proved that polarized light has a significant effect on the gene and protein expression of interleukin-6 (IL-6), a central regulatory molecule of acute inflammation, reducing IL-6 production in circulating blood monocytes while increasing that in human B lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that the absolute count of total lymphocytes and CD3 + CD4 + T cells increased significantly after 28 days of exposure to polychromatic VIS (540–780 nm) irradiation in adult humans (18 males, 15 females) [41], and also specific 710-nm light irradiation to the whole body of animals increased T cell subset populations in the peripheral blood of rats [23]. Both previous studies suggest that a new phototherapeutic regimen might be promising for CD4 + T lymphocyte-mediated immune modulation therapy.…”
Section: Discussionmentioning
confidence: 99%